THE INTERACTION OF RADIOTHERAPY AND CHEMOTHERAPY IN BREAST CANCER TREATMENT - Füsun Tokatlı (European Journal of Breast Health, 2008)

(untitled)
Cytotoxic agents can increase the efficacy of radiation. Radiosensitizing effects (interaction within the radiation field) can be additive or supra-additive. Multiple mechanisms underlie radiosensitizing properties of cytotoxic agents and include increased radiation damage, inhibition of DNA repair, cell-cycle synchronization, increased cytotoxicity against hypoxic cells, inhibition of prosurvival pathways, and abrogation of rapid tumor cell repopulation. The agents, which have the most radiosensitizing effects, are cisplatin and paclitaxel. In addition to the classic cytotoxic agents with radiosensitizing properties several novel agents show promising interactions with radiation (e.g. EGFR inhibitors, antiangiogenic agents). Today, a sequential treatment is the standard treatment in the early stage breast cancer patients. However, concomitant chemotherapy and radiotherapy (RT) could be more appropriate to patients with high risk of recurrence, for example, in those with axillary lymph node metastases, close or positive surgical margins, large tumor size, young age and presence of lymphovascular invasion. Phase III trials are needed to define the benefits and the late effects of concomitant modern RT techniques (with 3 dimensional conformal, intensity modulated or image guided RT) with taxanes, capecitabine and targeted biologic agents in the adjuvant settings.